COST AND TIME PERFORMANCE ANALYSIS USING EARNED VALUE METHOD OF WHEAT SILO & PELLET SILO STRUCTURE REPAIR PROJECT PHASE 3 PT. ISM BOGASARI SURABAYA - Saputra, Edwin Octavianto; Muhammadun, Haris; Marleno, Risma (Transpublika Publisher, 2024)
The wheat silo and pellet silo structure repair project phase 3 by PT. ISM Bogasari Surabaya is an annual infrastructure maintenance and strengthening activity to support the smooth production process. For this reason, it is very important to be completed on time according to the contract in order to proceed to the next stage of repair and not experience delays that can result in cost overruns. In this study using EVM (Earned Value Method) analysis in overcoming these problems to determine the cost and time performance of implementation as the project progresses and the indicators used in the analysis include SV (Schedule Variance), CV (Cost Variance), SPI (Schedule Performance Index), CPI (Cost Performance Index), which aims to obtain the results of the calculation of ETC (Estimated To Complete) & EAC (Estimated At Complete) in the project completion cost forecast. While ETS (Estimated Temporary Schedule) and EAS (Estimated All Schedule) for project completion time forecast. Based on the results of the cost & time performance analysis carried out up to week 48, the CPI> 1 value shows that the project is experiencing savings and for time performance shows the SPI < 1 value, which means that the project is experiencing delays.